The Landslide Susceptibility Deliniation Using Analitycal Hierarchy Process in Banjarnegara Regency, Central Java - Risky Ramadhan; Widiatmaka Widiatmaka; Untung Sudadi (Pascasarjana, Universitas Negeri Padang, 2020)
Understanding the role of controlling factors and their geographical patterns is very important to predict landslide insecurity in the future. Until now, several qualitative, quantitative and semi-quantitative methods have been used to produce landslide-prone maps such as the Analytical Hierarchy Process (AHP). This study aims to: 1) identify landslide-prone factors in Banjarnegara Regency, 2) delineation spatial patterns of landslide-prone areas using the AHP method in Banjarnegara Regency. Factors that cause Banjarnegara Regency to be prone to landslides are slope, rainfall, soil type, lithology, land use, and land shape. Landslide-prone classification using AHP method produces 5 zones, namely very low prone zones (32.97%), low (19.69%), medium (25.31%), high (17.46%) and very high (4.55%). Landslide prone assessment using the AHP method has an accuracy rate of 81%, so the classification of landslide-susceptibility zones is categorized as high.